Using Tax Expenditures to Achieve Energy Policy Goals - Metcalf, Gilbert E (American Economic Review, 2008)
Tax expenditures are a major source of support for energy related to activities in the federal budget exceeding direct budget support for energy by a factor of nearly six. Focusing on the policy goals of reducing greenhouse gas emissions and petroleum consumption, I find these tax expenditures highly cost ineffective at best and counterproductive at worse. The tax credit for ethanol is an example of a cost ineffective subsidy. The cost of reducing CO2 emissions through this subsidy exceeded $1,700 per ton of CO2 avoided in 2006 and the cost of reducing oil consumption over $85 per barrel.